THE EFFECTIVENESS OF PEER FEEDBACK TECHNIQUE TO TEACH WRITING VIEWED FROM STUDENTS’ CREATIVITY - Andianto - Andianto (Premise: Journal of English Education and Applied Linguistics, 2014)
The objectives of the research are to examine whether: (1) Peer Feedback Technique is more effective than Teacher Feedback Technique to teach writing for the tenth grade students of SMA Muhammadiyah 1 Metro; (2) the students having high creativity have better writing ability than those having low creativity for the tenth grade students of SMA Muhammadiyah 1 Metro; and (3) there is an interaction between teaching techniques and students’ creativity to teach writing for the tenth grade students of SMA Muhammadiyah 1 Metro. The method applied in this research was an experimental study. It was conducted at the tenth grade students of SMA Muhammadiyah 1 Metro. It consists of six classes. The Samples were two classes of six classes chosen by using cluster random sampling. Each class was divided into two groups (the students having high and low students’ creativity). The data were analyzed by using Multifactor Analysis of Variance (ANOVA) test of 2 x 2 and Tuckey test. Based on the data analysis, there are some research findings that can be drawn. They are (1) Peer Feedback Technique is more effective than Teacher Feedback Technique to teach writing for the tenth grade students of SMA Muhammadiyah 1 Metro; (2) the students having high creativity have better writing ability than those having low creativity; (3) there is an interaction between teaching techniques and students’ creativity to teach writing in which Peer Feedback Technique is more appropriate to teach writing for students having high creativity and Teacher Feedback Technique is more appropriate to teach writing for students having low creativity. In short, the effect of teaching technique depends on students’ creativity.